Crossreactive mixed lymphocyte reaction determinants recognized by cloned alloreactive T cells. - Fathman, C G (1979)
We have isolated clones of alloreactive T cells by soft agar cloning of primed responder cells contained in serially restimulated, mixed lymphocyte cultures. These clones recognize unique mixed lymphocyte reaction (MLR) stimulating determinants present on (C57B/6 X A/J)F1 (B6A) spleen cells. By assaying the reactivity patterns of these clones on a panel of stimulator cells, we have identified at least three separate "specificities" of alloreactive T cell clones. Several clones exhibiting one of these three reactivity patterns have been isolated on many occasions from different experiments. Using such clones of alloreactive T cells, we have identified and are attempting to define crossreactive MLR stimulating determinants exhibited by a panel of stimulator cells. Recognition by certain clones of a shared MLR determinant(s) on B6A and DBA/2 and of the lack of this determinant(s) on B6 stimulator cells questions current concepts concerning the nature of MLR stimulating determinants and T cell recognition of alloantigens.